2011
DOI: 10.1016/j.yebeh.2010.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Generalized 3-Hz spike-and-wave complexes emanating from focal epileptic activity in pediatric patients

Abstract: We present two pediatric patients with an uncommon electrophysiological seizure propagation pattern. Both had dialeptic seizure as the main or only symptom. Case 1 had a small mass in the left medial temporal structures; Case 2 had no lesion in MRI. In both, EEG showed not only left temporal spikes but also bilaterally synchronous 3Hz spike-and-wave complexes (SWC) from onset and unusual secondarily generalized 3 Hz SWC patterns arising from the left temporal region. Case 1 was seizure-free following mass rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…It has been suggested that one should not overinterpret “generalized” EEG abnormalities (such as hypsarrhythmia, slow spike‐wave complexes, (poly‐)spike‐wave complexes, polyspikes, and electrodecrement) as arguments against surgical epilepsy treatment in lesional patients . Classical 3/s spike waves, however, were not explicitly mentioned in this study. The hypothesis that even classical 3/s spike‐wave complexes may emanate from focal epileptogenic lesions and can be cured by epilepsy surgery was postulated by Kakisaka et al (2011) . However, evidence for that hypothesis was based on only one patient with a temporomesial ganglioglioma in whom 3/s spike waves disappeared after epilepsy surgery. Although there are clinical and EEG diagnostic criteria for the diagnosis of generalized genetic epilepsies by ILAE, in cases with more irregular findings, the diagnosis remains difficult.…”
Section: Discussionmentioning
confidence: 80%
“…It has been suggested that one should not overinterpret “generalized” EEG abnormalities (such as hypsarrhythmia, slow spike‐wave complexes, (poly‐)spike‐wave complexes, polyspikes, and electrodecrement) as arguments against surgical epilepsy treatment in lesional patients . Classical 3/s spike waves, however, were not explicitly mentioned in this study. The hypothesis that even classical 3/s spike‐wave complexes may emanate from focal epileptogenic lesions and can be cured by epilepsy surgery was postulated by Kakisaka et al (2011) . However, evidence for that hypothesis was based on only one patient with a temporomesial ganglioglioma in whom 3/s spike waves disappeared after epilepsy surgery. Although there are clinical and EEG diagnostic criteria for the diagnosis of generalized genetic epilepsies by ILAE, in cases with more irregular findings, the diagnosis remains difficult.…”
Section: Discussionmentioning
confidence: 80%
“…Generalized discharges, resulting from secondary bilateral synchrony from a focal lesion, classically tend to be slower (<3 Hz) and have more irregular morphology. However, Kakisaka 8 reported one case with left mesial temporal lesion who had both temporal spikes and 3 Hz generalized spike-and-waves. The 3-Hz spike-and-waves disappeared after focal resection of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…As far as seizure semiology was concerned (3, 7), the presence of generalized seizures was related to unfavorable seizure outcomes ( OR = 1.84, 95% CI = 1.18–2.89, P = 0.008). It is reported that the immature structural and functional brains of younger children are more likely to experience generalized seizures than adult brains (12, 13). However, we did not determine any correlation between the presence of generalized seizures and unfavorable prognosis, although younger children constituted a large proportion of the cases in this study.…”
Section: Discussionmentioning
confidence: 99%